Paternal Occupational Exposure to Endocrine-Disrupting Chemicals as a Risk Factor for Leukaemia in Children: A Case-Control Study from the North of England. (16th July 2014) - Pearce, Mark S.; Baxter, Lucy R.; Parker, Louise
Abstract : Occupations with exposures to a variety of chemicals, including those thought to be potential endocrine disruptors, have been associated with an increased risk of leukaemia in offspring. We investigated whether an association exists between paternal occupations at birth involving such exposures and risk of leukaemia in offspring. Cases (n = 958 ) were matched, on sex and year of birth, to controls from two independent sources, one other cancers, one cancer-free live births. Paternal occupations at birth were classified, using an occupational exposure matrix, as having "very unlikely, " "possible, " or "likely" exposure to six groups of potential endocrine-disrupting chemicals. There was a significantly increased risk of acute nonlymphocytic leukaemia (ANLL) for polychlorinated organic compounds (OR 1.95, 95% CI 1.08–3.54) only in comparison with cancer-free controls, and for phthalates (OR 1.61, 95% CI 1.00–2.61) only with registry controls. A number of other, including inverse, associations were seen, but limited to one control group only. No associations were seen with likely paternal exposure to heavy metals. The associations identified in this study require further investigation, with better exposure and potential confounding (for example maternal variables) information, to evaluate the likelihood of true associations to assess whether they are real or due to chance.